Practical paediatric procedures - Henderson, Ruth Nia; Nichani, Sanjiv (Hodder Arnold, 2009)
"An invaluable multimedia tool for the paediatrician in training. Covering all the core diagnostic and therapeutic procedures that are essential knowledge for the trainee, the DVD and accompanying textbook are thoroughly integrated ... Each procedure is explained in the textbook and demonstrated on the DVD"--Container.